Understanding Dimensions, Contradiction Diagnosis, and Solution Path of Grain Security in China's Main Sales Areas in the New Era - Lei ZHANG; Shanshan FENG; Canfang ZHOU; Fei ZHOU; Li JING (Guangdong nongye kexue)
The study was conducted to enhance the food security guarantee capability of the main sales area in the event of major public safety emergencies, clarify the provincial grain production capacity and spatial changes in the production and sales areas, and further improve the national food security governance capacity and long-term mechanism under the background of the unified national market in the new era. Using ArcGIS technology combined with statistical analysis methods, the study analyzes the spatial evolution of grain production and area since the founding of the People's Republic of China, by taking the main grain production areas, main sales areas, as well as production and marketing balance areas in China as the research objects. The grain export rate of the main grain production areas from 2011 to 2023 is also calculated. Research has found that the net export of grain in China is more concentrated in four provinces including Heilongjiang, Henan, Shandong, and Anhui, while the grain export rates of provinces such as Sichuan, Jiangsu, Hubei, and Hunan continue to decline, and even show a tendency towards "regional sales". There are structural problems such as regional imbalance strengthening, production and sales mismatch, and grain and feed mismatch in China's food security. The tr ansportation distance between production and sales across provinces is too far and the normalized cost is high. The logistics channels are basically independent of each other, with poor interoperability and connectivity. It is proposed to further strengthen the requirement of ensuring a certain self-sufficiency rate in the main sales areas by adopting an all-encompassing approach to food, focus on improving the grain production and emergency reserve capacity of the main sales areas, establish a long-term mechanism for cross regional cooperation in grain "production and sales"; and enhance the endogenous enthusiasm of grain producers in the main sales areas and avoid "sports style" production methods.